Integrating Local Culture in Strengthening Pancasila Student Profiles: A Study on Cultural Literacy and Citizenship in Langsa City Elementary Schools - Rapita Aprilia; Inge Ayudia; Cut Kumala Sari; Senny Widia Oktari (MASI Mandiri Edukasi, 2026)
This study investigates the index of cultural and civic literacy among elementary school students in Langsa City, one of the most multicultural areas in Aceh Province, Indonesia. Using a mixed-methods, sequential, explanatory design, the research combined quantitative analysis of electronic education reports (e-raports) with qualitative exploration through interviews, observations, and document analysis. The quantitative findings revealed that of the four sample schools, two were categorised as moderate (yellow) and two as low (red), with an average index of 61.94%. These results indicate that students' mastery of cultural and civic literacy remains relatively low. The qualitative analysis highlighted several constraints in implementing the Projek Penguatan Profil Pelajar Pancasila (P5), including limited teacher training, a lack of thematic modules, and insufficient integration of local culture into learning activities. Schools predominantly adopted themes such as Entrepreneurship and Sustainable Lifestyle, while essential themes related to multicultural values, such as Bhinneka Tunggal Ika and Build Body and Soul, were not implemented. This study emphasises that, despite Langsa's rich cultural diversity, schools have yet to leverage local wisdom as a learning resource fully. The findings contribute to the discourse on cultural literacy by revealing paradoxes in multicultural contexts and provide practical recommendations for policymakers, educators, and local stakeholders to strengthen cultural and civic literacy as a foundation for social cohesion and national identity.